Description of the change from SLI to DLD in an English-speaking context - Llorenç, Andreu; Ahufinger, Nadia; Igualada, Alfonso; Sanz-Torrent, Mònica (Revista de Investigación en Logopedia, 2021)
Specific Language Impairment (SLI) is a neurodevelopmental disorder that affects around 7% of the population and that compromises the expression and/or understanding of oral language. However, it is a very unknown disorder for the general population. One of the factors that explain it is the great terminological dispersion that different professionals and diagnostic manuals have used to designate it. Given the great ignorance of the disorder and to reach an agreement regarding the nomenclature and diagnostic criteria Bishop et al. (2016, 2017) carried out two studies using the Delphi method in which different researchers, professionals that works with children with SLI as well as people from associations of relatives in the English-speaking countries (CATALISE consortium) participated. The main conclusions were the commitment to the terminological change towards the Developmental Language Disorder (DLD) as well as some diagnostic criteria that emphasize the functional difficulties that the disorder generates and its prognosis. This article makes an exhaustive review of all the implications that the results of these studies have on the conceptualization, evaluation and intervention of the disorder. In the Spanish-speaking community, it is necessary to carry out a work of reflection and consensus that agrees on the nomenclature and diagnostic criteria to adapt/adjust them to the sociocultural and linguistic context of all the Spanish-speaking countries.
Keywords: Specific Language Impairment; SLI; Developmental Language Disorder; DLD